Update on the Mechanism and Treatment of Sevoflurane-Induced Postoperative Cognitive Dysfunction - Wang, Cong-mei; Chen, Wei-can; Zhang, Yan; Lin, Shu; He, He-fan (Frontiers in Aging Neuroscience, 2021)
Sevoflurane is one of the most widely used anaesthetics for the induction and maintenance of general anaesthesia in surgical patients. Postoperative cognitive dysfunction (POCD) increases after sevoflurane anaesthesia, and patients with POCD exhibit lower cognitive abilities. POCD affects the lives of patients and places an additional burden on patients and their families. Understanding the mechanism of sevoflurane-induced POCD can allow better prevention and treatment of POCD. This paper reviews the diagnosis of POCD, introduces the animal model of POCD in clinical research, analyses the possible mechanism of sevoflurane-induced POCD, and summarises its advanced treatment methods.